The Scars Of Old Memories Impact On Human Psyche In Paula Hawkins’ The Girl On The Train - Moses Glorino Rumambo Pandin; Anindya Putri Wisnumurti (Universitas Airlangga, 2022)
Every human being in this world has its imperfection. An individual can change his or her personality according to experience. Every person has insecurities and anxieties that may cause behavior to change. This phenomenon is also represented in Paula Hawkins’s novel titled The Girl on the Train. The study aims to reveal the cause of Megan’s loss of her love one experience affect her current personality and to reveal Megan’s projection and displacement affect the relationship with her husband. The research used psychoanalytic criticism theory to analyze the novel The Girl on the Train. The primary datum of this study is the novel, which focuses on the expression and explanation related to the unconscious fears and defenses mechanism by the characters. The results showed that someone’s behavior would change after having a bad experience as well as losing the loved one. Moreover, when someone pressed them a lot for doing something that they do not want to. In order to overcome someone’s wound, a person will be releasing his or her wounds to other people.